2015
DOI: 10.1177/0973408215569112
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in National Policy on Education for Sustainable Development and Climate Change Education

Abstract: Climate change education (CCE) is a new phenomenon which is gaining increasing significance in the work of international organizations and international non-governmental organizations. Based primarily on a crossnational desk study of national policy documents relevant to CCE in 17 countries, which was commissioned by UNESCO to gain a robust contextualized understanding of national CCE policies to inform UNESCO's guidelines on CCE in the context of Education for Sustainable Development (ESD), this article argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 7 publications
2
37
0
Order By: Relevance
“…Pruneau et al 2003;McCaffrey and Buhr 2008;Whitmarsh 2008;Maibach et al 2010;Akerlof, Bruff, and Witte 2011;Corner and Randall 2011;Hart 2011;Skamp, Boyes, and Stanisstreet 2013;Hestness et al 2014;Busch and Rom an 2017;Drewes, Henderson, and Mouza 2018;Meehan, Levy, and Collet-Gildard 2018), education policy development, and barriers and critique, when faced with climate change as a 'wicked problem', 'super wicked problem ', or 'hyperobject' (McKenzie 2019, Saari andMullen 2018;cf. Lorenzoni, Nicholson-Cole, and Whitmarsh 2007;Hamilton 2011;Morton 2013;Laessøe and Mochizuki 2015;Moyson, Scholten, and Weible 2017;UNFCCC 2018).…”
Section: Learning Objectives For Achieving the Sdgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pruneau et al 2003;McCaffrey and Buhr 2008;Whitmarsh 2008;Maibach et al 2010;Akerlof, Bruff, and Witte 2011;Corner and Randall 2011;Hart 2011;Skamp, Boyes, and Stanisstreet 2013;Hestness et al 2014;Busch and Rom an 2017;Drewes, Henderson, and Mouza 2018;Meehan, Levy, and Collet-Gildard 2018), education policy development, and barriers and critique, when faced with climate change as a 'wicked problem', 'super wicked problem ', or 'hyperobject' (McKenzie 2019, Saari andMullen 2018;cf. Lorenzoni, Nicholson-Cole, and Whitmarsh 2007;Hamilton 2011;Morton 2013;Laessøe and Mochizuki 2015;Moyson, Scholten, and Weible 2017;UNFCCC 2018).…”
Section: Learning Objectives For Achieving the Sdgsmentioning
confidence: 99%
“…First, it remains far from being a requirement or capability of core educational institutions or professionals, starting with those that claim their work is aligned with advancing this particular work or that of the Sustainable Development Goals more broadly, let alone every institution or professional living in and through 'climate chaos' (see also Hicks and Bord 2001;Jickling 2013;Laessøe and Mochizuki 2015;Wynes and Nicholas 2017;Verlie 2019).…”
mentioning
confidence: 99%
“…Solutions to climate change tend to focus on mitigation and adaptation measures, and successful implementation of either strategy requires an informed and educated citizenry. Interest in education and climate change has increased in recent years [2] in part due to leadership efforts from organizations like the United Nations Education, Scientific, and Cultural Organization (UNESCO) that continue to advocate for educational efforts to respond to climate change [3]. Yet despite the notion of education's importance in responding to climate change, education is rarely mentioned in discussions of today's major climate solution strategies.…”
Section: Introductionmentioning
confidence: 99%
“…While the process of transferring the social innovation of ESD usually takes place differently not only in each country or region but also within different educational areas [25], setting up appropriate strategies is a complex task in general. National governments tend to choose so-called "soft" instruments, such as consultations, networking structures, and guidelines, and even "take the role as mediators or coordinators of an ongoing dialogue and cooperation on promotion of ESD" [26] (p. 36) to reach collective ownership.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous research has revealed some insights about the effects of such intermediary spaces of negotiation on the actors involved. For instance, several studies found that policymakers [26] (p. 39) or civil-society actors [31] (p. 422) became confused about their roles when working together for scaling ESD. Another study focused on the importance of trust, commitment, framing, and-most crucially-reflexivity when actors from different sectors are working together in multi-stakeholder governance networks and solving wicked sustainability problems [32].…”
Section: Introductionmentioning
confidence: 99%